The position of Algerian women in the family and modern society - Nabila Aissaoua; Wahiba Aissaoua (Social Sciences Journal, 2020)
Represents the growing presence of Algerian women in public life is one of the pillars of social and economic change experienced by Algeria since independence. Shows to keep up with Algerian women of course change a reflection of its active role in various fields, whether family or work, education or political life. This work focuses on identifying the social status of Algerian women in traditional society and in modern society, and the social changes in Algerian society on the one hand, and the position of the Algerian State and its policies towards the promotion of women to make them an active member of the community.